2018
DOI: 10.1111/apt.14856
|View full text |Cite
|
Sign up to set email alerts
|

Impact of patatin‐like phospholipase domain containing 3 rs738409 G/G genotype on hepatic decompensation and mortality in patients with portal hypertension

Abstract: SummaryBackgroundThe rs738409 C>G p.I148M variant in the patatin‐like phospholipase domain containing 3 (PNPLA3)‐gene promotes triglyceride accumulation in hepatocytes and hepatic stellate cell activation and has previously been linked to hepatic steatosis/liver fibrosis.AimTo investigate its impact on hepatic decompensation and (liver‐related) mortality in patients who had already developed portal hypertension. Moreover, we assessed its link with hepatic steatosis as evaluated by controlled attenuation parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
42
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 35 publications
(48 reference statements)
4
42
0
Order By: Relevance
“…This is consistent with published reports that 148M was not associated with metabolic changes in a study of over 100 metabolic measures . In another study of patients at high risk for cardiovascular events, 148M was inversely associated with total and low‐density lipoprotein cholesterol …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is consistent with published reports that 148M was not associated with metabolic changes in a study of over 100 metabolic measures . In another study of patients at high risk for cardiovascular events, 148M was inversely associated with total and low‐density lipoprotein cholesterol …”
Section: Discussionsupporting
confidence: 92%
“…(35) In another study of patients at high risk for cardiovascular events, 148M was inversely associated with total and low-density lipoprotein cholesterol. (36) Multiple studies found relationships of PNPLA3 I148M with NAFLD, but reported associations with mortality from liver disease or all causes are limited. In the Study of Health in Pomerania in North-Eastern Germany, 148M was associated with a 4-fold increase in the liver disease mortality hazard for men only, most likely attributable to small sample size, shorter followup time, and fewer events in women.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent issue of AP&T , Mandorfer and colleagues retrospectively evaluated the impact of the missense PNPLA3 ‐rs738409 C>G variant on liver‐related mortality in a cohort of patients with different underlying diseases and portal hypertension at the time of diagnosis . The authors observed that homozygous status of the risk G‐allele (rs738409‐GG) substantially increased mortality rates among patients with NAFLD/ALD two‐fold without influencing survival rates in patients with viral hepatitis.…”
mentioning
confidence: 99%
“…We thank Drs. Pirola and Sookoian for reviewing the role of the rs738409 C>G p.I148M variant in the patatin‐like phospholipase domain containing 3 ( PNPLA3 ) gene and its interaction with other genetic and nongenetic factors in modulating the course of (non‐alcoholic) fatty liver disease as well as for their insightful comments on our manuscript …”
mentioning
confidence: 99%
“…Importantly, all patients included in our study had portal hypertension, indicating ACLD . Moreover, we accounted for potential differences in the severity of liver disease at baseline by adjusting all our survival analyses for HVPG.…”
mentioning
confidence: 99%